The Influence Of Social Media Quality On Brand Image: A Case Study Of Endek Users In Denpasar City - I Gusti Agung Ayu Mas Suariedewi; I Wayan Chandra Adyatma; I Nyoman Angga Prabawa (Profesional Muda Cendekia Publishing, 2023)
The digital technology revolution on social media has occurred and is gradually changing consumer behavior and expectations. Currently, social media is used by various business units as a communication media strategy. Hence, social media as a set of online media platforms provides new ways not only for individuals but also for business-oriented organizations to promote and communicate their values ​​with their audience. The development of the industrial sector in the province of Bali, amounting to 8.15%, is the textile and clothing industry. The large number of business actors in the textile and clothing industry cannot be denied from the large market demand for textile and apparel products, one of which is endek cloth. In this regard, this research has a strategic role in identifying the important role of quality social media in enhancing the brand image of Galeri Bhumimi in the digital era, and intends to empower MSMEs to utilize digital channels effectively to enhance brand image. Data was collected using a questionnaire distributed to 100 respondents. The data analysis technique used path analysis and the SPSS Version 22 application. The results showed that the quality of social media had a positive and significant effect on brand awareness. The quality of social media has a positive and significant effect on brand image. Brand awareness has a positive and significant effect on brand image. Based on the results of the Sobel test the mediating effect, the brand awareness variable does not mediate between the quality of social media and brand image.